Flipchart Media And Video About Preventing Early Stunting In Improving Knowledge Of Moms In Integrated Healthcare Center Sempu Village Kediri Regency - Fardila Nur Alviani; Mayta Sari Dwianggitamawati (Universitas STRADA Indonesia, 2021)
The process of stunting or stunting a child in a poor area or area, occurs from about six months of age and continues until the child is 18 years old.The research objective was to analyze the influence providing health education using flipchart media and videos about preventing early stunting of the knowledge of mothers under five at Sumberpetung Integrated Healthcare Center, Sempu Village, Kediri Regency. The design of this research is experimental quantitative research with the focus of the research being directed at analyzing the effectsproviding health education using flipchart media and videos about preventing early stunting of the knowledge of mothers under five at the Sumberpetung Integrated Healthcare Center, Sempu Village, Ngancar District, Kediri Regencywith a population of 76 respondents and a sample of 39 respondents who were taken using the Accidental Sampling technique. The findings found thatalmost half of respondents have low category knowledge of 9 respondents (47.4%) before it is given flipchart education. Whileonce given flipchart education almost half of the respondents have knowledge of the moderate category of 8 respondents (42.1%). other than that almost half of respondents have low category knowledge of 9 respondents (47.4%) before being given video education. While after being given educational video Most of the respondents have moderate category knowledge of 11 respondents (57.9%).The results of the study used the test Independent t-test indicates that the p-value is 0.040 <0.05, then H0 is rejected and H1 is accepted, so it is concluded that there is differences in the effectiveness of providing health education using flipchart media and videos about preventing early stunting on the knowledge of mothers under five at Sumberpetung Integrated Healthcare Center, Sempu Village, Ngancar District, Kediri Regency.Parents, especially mothers, can understand well what to avoid in order to avoid stunting, and how to prevent stunting